PENGARUH MODEL PEMBELAJARAN KOOPERATIF TEKNIK MAKE A MATCH TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR IPS - Nyoman Tri Esa Putra (Purwadita : Jurnal Agama dan Budaya, 2019)
This study aims to determine the effect of the cooperative learning model make a matchtechnique on learning motivation and social studies learning outcomes in Class V students ofSD Cluster VII Kubu District, Karangasem Regency. The design of this study uses the basicpattern of The Posttest Only Control Group with a type of quasi-experimental. The study sampleamounted to 56 students. Data collected are learning motivation and social studies learningoutcomes. Data was analyzed using assisted MANOVA SPSS 17.00 for windows. The results ofthe study show that: First, the learning motivation of students who learn with cooperative learningusing the make a match technique is significantly better than students who follow learning withconventional models (F = 48.923; p <0.05). Second, social studies learning outcomes of studentsstudying with cooperative learning make a match techniques were significantly better thanstudents who followed learning with conventional models (F = 47.046; p <0.05). Third,simultaneously learning motivation and social studies learning outcomes between studentsstudying with cooperative learning make a match techniques were significantly better thanstudents who followed conventional learning models.